Hubungan Antara Konsep Diri dengan Perilaku Merokok pada Remaja Awal - Dewi Larasati; Indra Wahyudi; FX. Wahyu Widiantoro (LPPM Universitas Proklamasi 45, 2019)
The increasing numberof smokers in adolescents from year to year makes a bad impact on adolescents development that is learning achievment, mental health and physical health. Adolescents social relationns from the self-concept which it will determine the adolescents behavior amd making decisions, including the decision to smoke even though just try it. Self-concept is relationship of perception to him based on his interactions with environment, those are parents, friends of the same age, school environment, and the surrounding environment. Aims: this research aimed to know the relationship between self-concept with smoking behavior in early adolescents. Method: this research used quantitative methods and qualitative methods. Quantitative methods by collecting data using a scale, and to enrich the result using qualitative methods that is interviews to four subject who smoke the most intensity. Result: the result from this reasearch shows that value r count is -0,372 > r tabel 0,288, its means there is a significant negative relationship between self-concept with smoking behavior in early adolescent. There are four subjects with high smoking rate of 12 cigarettes a day, then excavated through interviews. The conclusion is that the teen’s self-concept is low, the higher the smoking behavior. Factors that influence teenagers smoking are personal characteristic, modeling, peer pressure, and addiction. Keywords: Self-Concept, Smoking Behavior.